Can the following equation be factored?

x^2 - 12 + 27

### 1 Answer | Add Yours

For the first example, we'll have to combine like terms:

x^2 + (-12 + 27) = x^2 + 15

We'll put the quadratic equal to zero:

x^2 + 15 = 0

We'll subtract 15:

x^2 = -15

x1 = sqrt(-15)

Since sqrt -1 = i, we'll get:

x1 = i*sqrt 15

x2 = - i*sqrt 15

We'll factorize the equation:

x^2 + 15 = (x - x1)(x - x2)

**x^2 + 15 = (x - i*sqrt 15)(x + i*sqrt 15)**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes